Toxic Effects of Trichloroethylene on Rat Neuroprogenitor Cells - Salama, Mohamed M.; El-Naggar, Doaa A.; Abdel-Rahman, Rania H.; Elhak, Seham A. G. (Frontiers in Pharmacology, 2018)
Trichloroethylene (TCE) is a common volatile organic solvent which is considered as an ubiquitious environmental pollutant. It is claimed to be a developmental neurotoxicant. Our group evaluated its impact previously on three dimensional neurospheres in vitro This work aims to investigate the neurotoxic effects of lower concentrations of TCE on the same system. To perform the experiment, neural progenitor cells were obtained from the brains of nine newborn rats, then these cells were cultured in both growth and differentiation media to get the neurospheres. Cell cultures were divided into two groups: Group 1 (control), group 2 (exposed to 0.25 TCE ). Neurospheres were photographed at different durations and assessment of the morphological changes such as proliferation and differentiation of neurospheres was done. In addition, cell viability, apoptosis and necrosis were analyzed using flow cytometry to clarify the mechanism of involved cytotoxicity. The results revealed that TCE-treated neurospheres showed significantly decreased proliferation on days 7 and 14. These cells failed to show the neurogenic differentiation seen in the neurospheres of the control group. Furthermore, neurospheres exposed to TCE showed a highly significant decrease in viability and significant increase of the number of apoptotic cells. The present work confirmed that TCE, at lower doses, caused neurotoxic effects in 3D neurosphere model through affection of neural proliferation and differentiation as well as disturbance of cell viability and apoptosis.